COMPARISON OF PHONOLOGICAL AND MORPHOLOGICAL ACQUISITION PROCESSES IN CHILDREN - Sinaga, Yenni Adelina; Damanik, Bernieke Anggita Ristia (Sindoro: Cendikia Pendidikan, 2025)
This study explores the comparison between phonological and morphological acquisition processes in children, focusing on the developmental trajectories and underlying cognitive mechanisms. Phonological acquisition refers to the process by which children learn the sounds of their language, while morphological acquisition involves the learning of word structure, including prefixes, suffixes, and grammatical markers. Both processes are essential for language development but differ in complexity and the ways they interact with cognitive, social, and environmental factors. This paper reviews existing research on the timing, stages, and patterns of both phonological and morphological development, identifying key milestones and factors influencing these processes. The study examines how phonological and morphological systems are interrelated, with phonological awareness potentially aiding morphological learning, and vice versa. Through an analysis of longitudinal and cross-sectional studies, the paper outlines the interplay between these domains and their role in overall language acquisition. The findings suggest that while phonological acquisition typically precedes morphological development, there is significant overlap and interdependence between these areas. The paper concludes with implications for language teaching and intervention strategies, emphasizing the importance of considering both phonological and morphological development in fostering optimal language skills in children.